Measuring School Climate: Invariance across Middle and High School Students. Issue 1 (18th December 2019) - Waasdorp, Tracy Evian; Lindstrom Johnson, Sarah; Shukla, Kathan D; Bradshaw, Catherine P
Abstract: Positive school climate has been consistently associated with many desirable student outcomes in both middle and high schools. However, there has been little work comparing the perceptions across these two school settings. The U.S. Department of Education conceptualized a three-factor model for school climate consisting of safety, engagement, and environment. Drawing on data from 29, 720 middle and 34, 950 high school students, the fit of the three-factor model was examined for measurement invariance, to explore whether the measure functioned similarly across both middle and high schools. The results indicated measurement invariance, which suggests that practitioners and researchers can confidently compare findings across middle and high schools to inform local decision making related to school-based programming. A series of multilevel analyses also explored the extent to which perceptions of school climate differed for middle and high school students; these results generally indicated that middle school students perceived the school more favorably than high school students. Implications of these findings for social workers are considered.